The effect of polyvinyl alcohol addition on the solid carbon infusion in zirconia-toughened alumina - Roshidan, Nursamirah; Manshor, Hanisah; Rozhan, Alya Naili; Ahmad Azhar, Ahmad Zahirani (Trans Tech Publications Ltd, 2022)
This study examines the effect of adding various amount of polyvinyl alcohol (PVA) from 1 wt. % to 5 wt. % as function to produce porosity of the microstructure on Zirconia-Toughened Alumina (ZTA). Porosity is required in this study which aims to increase the efficiency of carbon infiltration on the porous composite through chemical vapor infiltration (CVI). Moreover, carbon production from empty fruit bunch (EFB) was used as a reinforcement on ceramic composites in this system. The microstructure of samples was characterised by using scanning electron microscopy (SEM). The density shows the lowest at 2.864 g/cm3 when the percentage of binder is increased at 4wt.% of PVA without carbon infiltration but shows the highest density value which is 4.107 g/cm3 after carbon is infiltrated. Vickers hardness was used to identify the hardness of samples. It was found that ZTA composite with infiltrated carbon has better hardness (2053HV) with addition of 4wt.% of PVA. However, firing shrinkage showed no effect on the composite with or without carbon infiltration. The structure of crystalline carbon in composite was analyses by X-Ray Diffraction (XRD). Nevertheless, no peak for carbon is observed due to low carbon content and another alternative such as Raman spectroscopy was used to identify the presence of diffused carbon. Based on the result, carbon infiltration on composite will produce better physical and mechanical properties with the help of binders that produce pores for carbon to infiltrate.